If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -6) = 3x Reorder the terms: 5(-6 + x) = 3x (-6 * 5 + x * 5) = 3x (-30 + 5x) = 3x Solving -30 + 5x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -30 + 5x + -3x = 3x + -3x Combine like terms: 5x + -3x = 2x -30 + 2x = 3x + -3x Combine like terms: 3x + -3x = 0 -30 + 2x = 0 Add '30' to each side of the equation. -30 + 30 + 2x = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 2x = 0 + 30 2x = 0 + 30 Combine like terms: 0 + 30 = 30 2x = 30 Divide each side by '2'. x = 15 Simplifying x = 15
| 4(2x-1)=2(3x+6) | | .8=-.57 | | 18=7x+7x+4 | | 23x+1=36x+2 | | n-13=-10 | | 2(2x+4)=2x+24 | | n+33=50 | | 0.07x+4.59=4.73 | | 8y+4=3y | | 3=-3x+x+1 | | 7+2y=2y-2 | | 1/3(18y-6)=-5/8(12-6y) | | .75-.3z=.25 | | b-8+8b=18 | | 5x^2-2y+4=0 | | X+79=119+x | | 5(6x-2)-8=30x-18 | | 7x-3y=-20 | | 30=7x+5-2x | | 8(5d-9)= | | 9+1/4b=7 | | n-15= | | 9x+7=11x-7 | | 2.9=5.6-0.3x | | 7x-=-7 | | 4(9c+3)= | | 129x-19x=479 | | (3x-2)(5x-5)= | | 95=6x+7x-9 | | 15x+10=17x-4 | | logax=1.5 | | 54843hgyf=486vh |